Aloe : and other poems - Bridge, Diana (Auckland University Press, 2009)
Divided into four distinct sections, this collection of poetry draws inspiration from the natural world while dissecting the concepts of loss, hesitancy, generation, and repetition. Exploring how everything may be turned into words, this intriguing anthology also demonstrates how those words themselves may enact life. Additional voices and stories are used to convey psychological and physical suffering?utilizing the characters of the Furies, Sylvia Plath, and Medea?as well as the trauma and delight of birth and the curious reappearance of family traits. The final section is inspired.